A risk assessment framework based on ergonomic methods and AHP for prioritizing interventions to prevent container terminal operator's musculoskeletal disorders. (March 2023) - Cimino, Antonio; Gnoni, Maria Grazia; Longo, Francesco; Nicoletti, Letizia
Highlights: Ergonomic risk assessment in lashing and unlashing operations within container terminals. Identification of workers hazardous activities within container terminals. Process mapping and task analysis to prevent operators' musculoskeletal disorders. Simulation coupled with ergonomic methods and analytical hierarchy process. Analytical Hierarchy Process as decision making methodology for operations ranking and priority of interventions. Abstract: Tasks and procedures involving lashing/unlashing operators have evident ergonomic criticalities but looking at the scientific background and on actual regulations there is a lack of attention toward procedures for a full ergonomic risk assessment. There are no scientific articles, no normative and standards that report ergonomic assessments for lashing and unlashing operations. According to this research gap, the proposed research seeks to contribute at different levels: carrying out a context analysis on how lashing and unlashing operations are carried out; identifying tools and methodologies that can support a comprehensive ergonomic analysis; combining the elements mentioned above in a risks assessment framework for ergonomic evaluation and prioritization. While pursuing such goals, the authors came up with a risk assessment framework based on simulation coupled with ergonomic methods and Analytical Hierarchy Process (AHP). An application of the framework has been conducted in an Italian container terminal in 2021. First, processes and tasks have been analyzed to develop a simulation model capable of reproducing the evolution over the time of the real system. As next step, the ergonomic issues related to lashing/unlashing operations have been identified by applying the ergonomic methods through the simulation model. Finally, AHP has been used to rank, in an analytical way, critical ergonomic operations and to establish priority of interventions. The identification of critical ergonomic issues along with their analytical prioritization provide operations management as well as normative and standard makers with meaningful inputs towards greater standardization of procedures, based on ergonomic factors, in container terminal sector.